2020
DOI: 10.3390/s20143860
|View full text |Cite
|
Sign up to set email alerts
|

Object Distance Estimation Using a Single Image Taken from a Moving Rolling Shutter Camera

Abstract: This paper proposes a technique to estimate the distance between an object and a rolling shutter camera using a single image. The implementation of this technique uses the principle of the rolling shutter effect (RSE), a distortion within the rolling-shutter-type camera. The proposed technique has a mathematical strength compared to other single photo-based distance estimation methods that do not consider the geometric arrangement. The relationship between the distance and RSE angle was derived using the camer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Invisible perturbation: By exploiting the unique characteristics of cameras, camera-based approaches have demonstrated successful adversarial attacks in the physical domain. Sayles et al [50] made a significant discovery regarding the rolling shutter effect commonly found in consumer-grade cameras, including cell phones [145]. They found that this effect can generate precise striping patterns that manifest in captured images.…”
Section: Imaging Device Manipulation-based Attackmentioning
confidence: 99%
“…Invisible perturbation: By exploiting the unique characteristics of cameras, camera-based approaches have demonstrated successful adversarial attacks in the physical domain. Sayles et al [50] made a significant discovery regarding the rolling shutter effect commonly found in consumer-grade cameras, including cell phones [145]. They found that this effect can generate precise striping patterns that manifest in captured images.…”
Section: Imaging Device Manipulation-based Attackmentioning
confidence: 99%
“…Digital cameras use rolling shutter technique to obtain high resolution images at higher rate and at cheaper price [3,29]. Rolling shutter technology is used in majority of consumer-grade cameras, such as the ones used in cellphones [21], AR glasses [34] as well as for machine vision [1,2].…”
Section: Human Visionmentioning
confidence: 99%
“…The movement of the UAV during image acquisition causes a short delay between the top and bottom of the generated image (Gazioğlu et al, 2017). This causes a kind of image distortion known as the rolling/jelly artifact, which negatively affects the accuracy of the DEM produced by the structure from motion (SfM) approach (Bruno and Forlani, 2023;Incekara and Seker, 2021;Kim et al, 2020). On the other hand, depending on the stabilization of the UAV platform, its speed and the exposure time of the camera during image acquisition, motion blur may occur and SfM suffers from this distortion as well (Peng et al, 2022;Sieberth et al, 2015;Teague and Chahl, 2023).…”
Section: Introductionmentioning
confidence: 99%